China's WTO accession: conflicts with domestic agricultural policies and institutions - Colby, Hunter; Diao, Xinshen; Tuan, Francis (International Food Policy Research Institute, 2001)
This analysis examines the implications of WTO accession for China’s domestic policies and institutions by identifying some of Chinese agricultural policies and institutional arrangements that may generate conflicts with WTO requirements and analyzing the nature and extent of the conflict that may be introduced by WTO accession. We differentiate three alternative ways that China’s current domestic policy or institutions may conflict with or be incompatible with WTO accession: (1) the domestic policy or institution is expressly prohibited by WTO rules and principles; (2) the changes required by WTO accession impose additional costs on the government such that the existing policy or institutions are difficult to sustain; and (3) the changes required for WTO accession reduce the effectiveness of the policies or institutions.